Novel Chimeric Protein Vaccines Against Clostridium difficile Infection - Wang, Shaohui; Wang, Yuanguo; Cai, Ying; Kelly, Ciaran P.; Sun, Xingmin (Frontiers in Immunology, 2018)
Clostridium difficile infection (CDI) is the leading cause of world-wide nosocomial acquired diarrhea in adults. Active vaccination is generally accepted as a logical and cost-effective approach to prevent CDI. In this paper, we have generated two novel chimeric proteins; one designated Tcd169, comprised of the glucosyltransferase domain (GT), the cysteine proteinase domain (CPD) and receptor binding domain (RBD) of TcdB, and the receptor binding domain of TcdA; the other one designated Tcd169FI, which contains Samlnonella typhimurium flagellin (sFliC) and Tcd169. Both proteins were expressed in and purified from Bacillus megaterium. Point mutations were made in the GT (W102A, D288N) and CPD (C698) of TcdB to ensure that Tcd169 and Tcd169FI were atoxic. Immunization with Tcd169 or Tcd169Fl induced protective immunity against TcdA/TcdB challenge through intraperitoneal injection, also provided mice full protection against infection with a hyper-virulent C. difficile strain (BI/NAP1/027). In addition, inclusion of sFlic in the fusion protein (Tcd169Fl) enhanced its protective immunity against toxin challenge, reduced C. difficile numbers in feces from Tcd169Fl-immunized mice infected C. difficile. Our data show that Tcd169 and Tcd169FI fusion proteins may represent alternative vaccine candidates against CDI.